EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen